2024
DOI: 10.1111/all.16001
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of allergic rhinitis nasal transcriptome by dupilumab and allergy immunotherapy

Matthew F. Wipperman,
Kaitlyn M. Gayvert,
Amanda Atanasio
et al.

Abstract: BackgroundNasal epithelial cells are important regulators of barrier function and immune signaling; however, in allergic rhinitis (AR) these functions can be disrupted by inflammatory mediators. We aimed to better discern AR disease mechanisms using transcriptome data from nasal brushing samples from individuals with and without AR.MethodsData were drawn from a feasibility study of individuals with and without AR to Timothy grass and from a clinical trial evaluating 16 weeks of treatment with the following: du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…This is in agreement with previous studies which found ALOX15 to be downregulated after dupilumab treatment. 38 At the same time, CYP1B1 encoding cytochrome P450, which is responsible for metabolizing arachidonic acid to 20-hydroxyeicosatetraenoic acid and has been shown to lead to relaxation of airways 20,39 , was strongly downregulated during provocation one but not provocation two. This could indicate that long-term treatment with the anti-IL-4Rα inhibitor dupilumab may ameliorate the imbalance in the arachidonic acid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies which found ALOX15 to be downregulated after dupilumab treatment. 38 At the same time, CYP1B1 encoding cytochrome P450, which is responsible for metabolizing arachidonic acid to 20-hydroxyeicosatetraenoic acid and has been shown to lead to relaxation of airways 20,39 , was strongly downregulated during provocation one but not provocation two. This could indicate that long-term treatment with the anti-IL-4Rα inhibitor dupilumab may ameliorate the imbalance in the arachidonic acid pathway.…”
Section: Discussionmentioning
confidence: 99%